Analysis of The Influence of Company Social Responsibility (CSR), Leverage, and Company Measure on Tax Avoidance (Study on Manufacturing Companies Listed on The Bursa Efek Indonesia (BEI) in 2017-2020) - Lenawati Haryanto; Inayah Ramadhani (Majalah Ilmiah Bijak, 2023)
This study aims to determine the influence of Company Social Responsibility (CSR), Leverage, and Company Size on Tax Avoidance either simultaneously or partially. In this study, the independent variable CSR is measured using 91 indicators of CSR disclosure, leverage is measured using debt to equity, and corporate size is measured using the natural logarithm of total sales. The dependent variable Tax Avoidance is measured using the Effective Tax Rate (ETR). The object of this research is the coal mining sub-sector which is listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with a total sample of 11 (eleven) corporate with an research period of 2017-2020. This study uses multiple linear regression analysis method. Based on the results, it shows that Company Social Responsibility (CSR), Leverage, and Company Size simultaneously have no influence on Tax Avoidance. CSR, and Leverage have no influence and are not significant on Tax Avoidance, while Company Size has a positive influence on Tax Avoidance.